Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 7 - Algebraic Fractions - Chapters 1-7 Cumulative Review Problem Set: 40

Answer

$2x(x+6)(x-9)$

Work Step by Step

Since $2x$ is common to every term of the expression, we first factor out $2x$: =$2x^{3}-6x^{2}-108x$ =$2x(x^{2}-3x-54)$ Now, we find out that the equation in the parenthesis represents a trinomial which can be factorized by using the rules of factoring trinomials: =$2x(x^{2}-3x-54)$ =$2x(x^{2}+6x-9x-54)$ =$2x[x(x+6)-9(x+6)]$ =$2x[(x+6)(x-9)]$ =$2x(x+6)(x-9)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.